Pengaruh Current Ratio, Debt to Equity Ratio, dan Inventory Turnover Terhadap Return On Asset (Studi pada Perusahaan Manufaktur Subsektor Food and Beverage yang terdaftar di Bursa Efek Indonesia Periode 2020-2022) - Kurniawati, Firlia Ayuk; Waluyo, Dwi Eko (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study examines the impact of current ratio, debt equity ratio, and inventory turnover on Return On Assets (ROA) in Food and Beverage companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. The data used is quarterly data obtained directly from the companies' published financial statements. The sampling technique used was purposive sampling, resulting in a sample of 17 companies in the Food and Beverage sub-sector and a total of 204 data points. The study employed quantitative analysis, specifically panel data regression using Eviews 12. The findings revealed that the current ratio has insignificant effect on ROA, debt equity ratio and inventory turnover had a positive and significant impact on ROA. Simultaneous test result (F test) show that current ratio, debt to equity ratio and inventory turnover have a positive and significant effect on return on asset.